Pengaruh literasi keuangan, efikasi diri, dan pendapatan orang tua terhadap perilaku pengelolaan keuangan - Ramadana, Melda; Munadiati; Hisan, Khairatun (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
Having good financial management behavior can help students achieve positive finances and be able to overcome any challenges, especially in terms of financial problems that are more complex than those of their parents. This study aims to determine the effect of Financial Literacy, Financial Self-Efficacy and Parental Income on Financial Management Behavior. The subjects of this study were students of the Islamic Financial Management Study Program at IAIN Langsa. This research is a quantitative research with a sample of 72 respondents. The sampling technique uses nonprobability sampling. Data analysis technique using multiple regression analysis. The results of this study indicate that partially Financial Literacy (X1) has a negative and insignificant effect on Financial Management with a significant value of 0.174. Partially Financial Self Efficacy (X2) has a positive and significant effect on Financial Management with a significant value of 0.000. Partially Parental Income (X3) has a negative and insignificant effect on Financial Management with a significant value of 0.153. Simultaneously Financial Literacy, Financial Self Efficacy and Parental Income have a positive and significant effect on Financial Management Behavior with a significant value of 0.000. The Adjusted R Square value is 0.417 or 41.7% which means that Financial Management Behavior can be explained by Financial Literacy, Financial Self-Efficacy and Parental Income and the remaining 58.3% can be explained by other factors not examined in this study.